(untitled) (Experimental biology, 2016)
This paper shows the results of quantitative content of essential oils (EO) in wild grow species from the fam. Apiaceae Lindl.: Carum carvi, Seseli buchtormense, fam. Lamiaceae Lindl.: Marrubium vulgare,Mentha arvensis, M. longifolia, Nepeta pannonica, Origanum vulgare и Ziziphora clinopodioides. Also added the results of content EO of cultivated spe¬cies from fam. Lamiaceae under foothill conditions of Transe-Ili Alatau. Depending of plant ages observed the changes of quantitative content of EO for Origanum vulgare, Mentha arvensis, M. longifolia. This study let us reveal more valuable wild grow aromatic species of Kazakhstan, and isolated EO of Seseli buchtormense, Marrubium vulgare will be continued for further chemical analysis.